Habitual Use of High-Heeled Shoes Affects Isokinetic Soleus Strength More Than Gastrocnemius in Healthy Young Females. (September 2016) - Farrag, Ahmed; Elsayed, Walaa
Background: Habitual use of high-heeled shoes (HHS) has been reported to negatively impact different body structures. However, few studies have investigated its effect on plantarflexor performance. The aim of this study was to investigate the effect of habitual wear of HHS and knee joint position (to isolate the function of the gastrocnemius) on the isokinetic performance of the plantarflexors and ankle joint range of motion (ROM). Methods: A high-heel (HH) group included 12 women (25.4 ± 4.8 y) who have been wearing HHS for ≥40 hours/wk and for at least a year. A control group (CTRL) had 12 women (21.3 ± 0.5 y) who have occasionally been wearing HHS for <10 hours/wk. Participants performed isokinetic (60 degrees/s) plantarflexion movements through a range set between 15 degrees dorsiflexion and 30 degrees plantarflexion. Ankle joint ROM and average peak plantarflexion torque and power were recorded in 2 knee joint positions, extension and 90 degrees flexion. Results: Overall, torque was significantly affected by knee position ( P = .04) and habitual use of HHS ( P < .001), whereas power was impacted by knee position only ( P < .001). Within each group, flexing the knee reduced isokinetic measurements. However, the reduction was greater for the HH group (torque: 54 Nm, power: 35.6 W) compared with the CTRL group (torque: 42 Nm, power: 32.5 W). Ankle joint ROM was significantly different between groups in knee flexion only. Conclusion: Flexing the knee limited the plantarflexor muscular performance and the limitation was more significant in habitual users of HHS compared to nonusers. Thus, it is concluded that habitual use of HHS impacts the contractile properties of soleus more than gastrocnemius. Clinical Relevance: The soleus is important for walking and anterior cruciate ligament protection. Thus, HHS users could be susceptible to injury and may need longer and more intensive posttraumatic rehabilitation. Therefore, clinicians should consider knee position when examining the plantarflexors of habitual HHS users.